Developing Task Persistence Skills in College Students with Hard of Hearing Using Strategic Content Learning - Charity Neejide Onyishi (Indonesia Approach Education, 2023)
Poor task persistence is a major inhibitor of effective learning among students with hearing impairment. This study investigated the effect of strategic content learning (SCL) on poor task persistence of students with hearing loss in Nigeria. The study adopted a pretest-posttest control group design. A total of 117 participants from four special schools for hearing impaired in South-East Nigeria completed a task persistence scale at pre-treatment, post-treatment, and follow-up. Intervention was carried out for nine weeks using strategic content learning program manual. Data collected were analyzed using repeated-measures analysis of variance, chi-square, and t-test. Results revealed that task persistence of hearing impaired college students of SCL group were significantly improved compared to those in waitlist control group at the end of the intervention. Follow-up tests conducted after three months and six months revealed that the significant improvement in task persistence of participants in the experimental group was sustained. Result of the current study show that SCL is an effective strategy straining approach that can improve students’ task persistence in different areas of learning. Further studies could be conducted in Nigeria and other countries to investigate the efficacy of SCL in improving self-efficacy and volition among diverse populations of students.